LITERATURE STUDY: DIGITAL MEDIA IN LEARNING TO IMPROVE MATHEMATICS LEARNING OUTCOMES IN PRIMARY SCHOOLS - Ghari Sulistiani; Endang M. Kurnianti; Uswatun Hasanah (STKIP Subang, 2024)
Student learning outcomes are very influential on the use of methods and media used in learning, because learning outcomes are used as a measurement tool of a learning assessment that has been carried out. The purpose of this study is to know digital media that can be used in mathematics learning. The method used is a literature study with reference to conceptual and relevant research results. Data collection is carried out by reviewing and describing articles and literature reviews. The results of the analysis show that digital media is very effective in improving mathematics learning outcomes in elementary.